The Effect of Organisational Climate and Organisational Commitment on Employee Job Satisfaction at PT PLN Palopo City - Suharti, Suharti; Priyani, Putu Devi; Bakhtiar, Bakhtiar; Edy, Khairunnisa; Erwina, Erwina (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Employees in carrying out their duties and responsibilities, of course, must have good competence in order to improve organizational performance. The study examines the effect of organizational climate and organizational commitment on job satisfaction, where the study aims to determine how much influence the organizational climate and organizational commitment have on employee job satisfaction at PT PLN Palopo City. This research uses a quantitative approach research method which is specifically causal associative in nature involving 41 PLN employees in Palopo City. The results obtained from this study that organizational climate and organizational commitment have a positive and significant effect on employee job satisfaction at PT PLN Palopo City. The implications that employees get in making a decision so that employees feel cared for and can create emotional employee attachment to the company, and can also increase employee job satisfaction, because employees think they have a contribution to the company and will increase the organizational commitment of PT PLN Palopo City employees.